Enhancement of the Role of Islamic Social Finance for Renewable Energy Project Financing in Indonesia - Purnadi, Purnadi; Afif, Ahmad; Rodoni, Ahmad; Mufraini, M. Arief; Warninda, Titi Dewi (Yayasan Riset dan Pengembangan Intelektual, 2025)
Renewable energy, being environmentally friendly, needs to see increased utilisation due to the detrimental effects of fossil fuel usage on human life. The government has promoted the Energy Transition programme, yet the adoption of renewable energy remains limited, primarily due to financing challenges and the economic viability of projects. The government cannot tackle this alone; it requires the support of financing schemes backed by social funds from the community. In this regard, aligning with the objectives of Shariah (maqasid shariah), the role of Islamic Social Finance can be enhanced within the concept of Islamic Blended Finance to fund renewable energy projects that have social and environmental impacts. The aim of this paper is to develop the role of Islamic Social Finance within Islamic Blended Finance and the necessary regulations, making it a feasible financing scheme that can offer an alternative solution to the funding challenges faced by renewable energy projects. Previous research is limited due to the relative novelty of the topic. This study employs a mixed-methodology approach, incorporating literature review supported by secondary data, as well as primary data from interviews with competent informants.